2013
DOI: 10.3389/fncom.2013.00088
|View full text |Cite
|
Sign up to set email alerts
|

Using a hybrid neuron in physiologically inspired models of the basal ganglia

Abstract: Our current understanding of the basal ganglia (BG) has facilitated the creation of computational models that have contributed novel theories, explored new functional anatomy and demonstrated results complementing physiological experiments. However, the utility of these models extends beyond these applications. Particularly in neuromorphic engineering, where the basal ganglia's role in computation is important for applications such as power efficient autonomous agents and model-based control strategies. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 69 publications
3
49
0
Order By: Relevance
“…13, which means that we need to ensure that our system behaves in a similar manner to the actual biological system. We found that the NS employed in our study could reproduce most of the dynamic characteristics of the BG, as also demonstrated in the study by Thibeault and Srinivasa (2013). Thus, our proposed hardware platform can reproduce most of the biological dynamics of the BG with a considerably high level of precision and reliability.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…13, which means that we need to ensure that our system behaves in a similar manner to the actual biological system. We found that the NS employed in our study could reproduce most of the dynamic characteristics of the BG, as also demonstrated in the study by Thibeault and Srinivasa (2013). Thus, our proposed hardware platform can reproduce most of the biological dynamics of the BG with a considerably high level of precision and reliability.…”
Section: Discussionsupporting
confidence: 64%
“…In PD, a rhythmic synchronization of the mean output from the BG nuclei occurs due to the reduction in tonic and phasic dopamine, which causes a decrease in the ability of TC neurons to relay the depolarizing input current (Thibeault & Srinivasa, 2013). This loss of the relay ability is one of the major problems in many clinical PD cases (Putzke et al, 2003).…”
Section: F Ig 1 Herementioning
confidence: 99%
See 1 more Smart Citation
“…As shown before by this step can be performed also in neuroVIISAS using a hybrid neuron model (Thibeault and Srinivasa 2013) in the NEST simulation engine (Gewaltig and Diesmann 2007).…”
Section: Organization Of Connections In a Hierarchy Of Regionsmentioning
confidence: 99%
“…One of the very-well-explored disease-related circuits is the model of basal ganglia dysfunction in PD [ 163 , 164 ]. The architecture of corticobasal ganglia-cortical loops [ 165 ] is in fact a reconstructed network, with interactions being projections of different neuronal subtypes to basal ganglia and cortical regions [ 166 ]. Here, the disturbance of these mapped circuits may be assessed using the technique of recording neuronal activity in local brain areas, called electroencephalography ( EEG) .…”
Section: Identifi Cation and Connecting Of Candidate Areasmentioning
confidence: 99%